Computer-Assisted Career Counseling: Dilemmas, Problems, and Possible Solutions - Gati, Itamar (Journal of counseling and development, 1994)
Computer‐assisted career guidance systems (CACGSs) are one of the available tools used to facilitate the career decision‐making process of deliberating counselees. The development and utilization of these systems have raised dilemmas and problems that the author discusses from the viewpoint of information‐processing and decision theory. These dilemmas involve (a) the occupational data base, (b) the complexity of the career decision‐making process, (c) the effectiveness of the dialogue, and (d) the context in which the CACGS is embedded. After describing and analyzing each problem or dilemma, possible ways to overcome, circumvent, or at least minimize it are explored. The relevance for face‐to‐face career counseling is also discussed.